EXPLORING TEACHERS’ STRATEGIES IN TEACHING SPEAKING SKILLS AT SMP NEGERI 3 LOLOFITU MOI - Mewi Dinda Arcila Waruwu; Afore Tahir Harefa; Elwin Piarawan Zebua; Kristof Martin Efori Telaumbanua (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to describe the strategies used by teachers in teaching speaking skills at SMP Negeri 3 Lolofitu Moi and to determine how teachers choose the strategies used in the learning process. This study uses a qualitative research method with a descriptive qualitative type. Research data were obtained through observation, interviews, and documentation of English teachers and students. The research instruments consisted of observation sheets and interview guidelines used to collect information related to the application of speaking learning strategies in the classroom. The collected data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that the dominant strategies used by teachers were group discussions and role-playing. These strategies were proven to encourage students to be more active, confident, and able to express their ideas in English. Teachers also provided clear instructions, practical examples, and created a supportive classroom atmosphere so that students were more motivated to speak. In addition, teachers adjusted learning strategies according to student needs and classroom conditions. However, the variety of strategies was still limited, so it was recommended that teachers develop other strategies such as storytelling, simple debates, language games, and digital media to enrich the learning experience of students.